The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1080/01418610208239637
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of deformation bands in fatigued copper single crystals

Abstract: A bstractThe features of the deformation bands (DBs) in copper single crystals under cyclic straining were surveyed. A simple model was proposed to account for the formation of DBs. In this model, both crystal rotation and dislocation density variation induced by cyclic straining were considered. The gradual lattice rotation caused by tension and compression irreversibility is the main driving force for the formation of DBs. The drastic release of mobile dislocations resisted by the primary slip bands is the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 30 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…Reorientation is consistent with a recent analysis of slip asymmetry in cyclic deformation of fcc crystals [8], which showed that for the case of fully reversed loading, a single crystal reorients such that during the tensile half-cycle, the loading axis rotates towards the primary slip direction, [011], and during the compressive half-cycle, it rotates towards the normal to the primary slip plane, ) 1 1 1 ( . In particular, surface topography was observed to occur in only selected regions of stressed lines, and only certain grains showed growth and reorientation.…”
Section: Thermomechanical Fatigue Of Al-1si Interconnectssupporting
confidence: 89%
“…Reorientation is consistent with a recent analysis of slip asymmetry in cyclic deformation of fcc crystals [8], which showed that for the case of fully reversed loading, a single crystal reorients such that during the tensile half-cycle, the loading axis rotates towards the primary slip direction, [011], and during the compressive half-cycle, it rotates towards the normal to the primary slip plane, ) 1 1 1 ( . In particular, surface topography was observed to occur in only selected regions of stressed lines, and only certain grains showed growth and reorientation.…”
Section: Thermomechanical Fatigue Of Al-1si Interconnectssupporting
confidence: 89%
“…DBII are bands of localized deformation along $ 101 È É planes, perpendicular to the more common DBI deformation bands formed along {111} planes of the primary active slip system. DBI and DBII develop due to a gradual increase of lattice rotations and therefore they often appear together, in conjugate orientations related to each other, and are Philosophical Magazine 273 observed in a broad range of orientations including single and double slip crystals [14,24,25]. Veins, cells and dislocation wall structures are the most common patterns in the h111i region of orientations and they appear in the order of increasing strain amplitude [25,26].…”
Section: Introductionmentioning
confidence: 97%
“…The strain ranges realized in the cyclic torsion tests to be reported exceeded logarithmic strains of 0.1. Not many LCF examinations using such large cyclic strains are available in the literature for pure copper . The LCF behaviour will be explained in this study on the basis of heat generation and microstructural changes.…”
Section: Introductionmentioning
confidence: 99%
“…Not many LCF examinations using such large cyclic strains are available in the literature for pure copper. [13][14][15][16][17] The LCF behaviour will be explained in this study on the basis of heat generation and microstructural changes.…”
Section: Introductionmentioning
confidence: 99%